Aid for development of international trade - Bjelić Predrag; Popović-Petrović Ivana (Međunarodni Problemi, 2012)
The development of international trade was very impressive in the second half of 20th century. But even with these great development opportunities that growth of international trade can bring the small number of developed economies had succeeded to ripe benefits from it in order to develop their economies and reduce poverty. Even with the establishment of the World Trade Organization it was apparent that developing countries need assistance in order to integrate fully in international trade system. The Aid for Trade, which is a part of Official Development Assistance focusing on trade, has an aim to help developing countries build their trade capacity and the transport infrastructure so they can use trade as a powerful engine for economic growth. This paper set out to describe this new programme of trade aid developed under the auspices of WTO, as a multilateral project, to point out the readiness of donor countries and aims of beneficiary countries. But we will explore the linkages of Aid for Trade programme with bilateral and regional aid initiatives in the area of trade. [Projekat Ministarstva nauke Republike Srbije, br. 179029: Srbija u savremenim međunarodnim odnosima: Strateški pravci razvoja i učvršćivanja položaja Srbije u međunarodnim integrativnim procesima - spoljnopolitički, međunarodni ekonomski, pravni i bezbedonosni aspekti]